HUBUNGAN PENGETAHUAN DENGAN TINDAKAN DETEKSI DINI KANKER SERVIKS MELALUI METODE PAP SMEAR DI RSUD EMBUNG FATIMAH KOTA BATAM - Acholder Tahi Perdoman Sirait; Malahayati Rusli Bintang; Winda Jaya (Universitas Batam, 2026)
Background: Cervical cancer is a leading cause of death among Indonesian women, mainly due to late diagnosis. Pap Smear is an effective early detection method, yet its coverage remains low despite frequent education efforts. Women's knowledge is believed to influence screening decisions. Methods: A descriptive correlative study with a cross-sectional approach was conducted on 96 married women aged 20–65 years, selected via purposive sampling. Data were collected through questionnaires and analyzed using Fisher Exact Test. Results: Most respondents had good knowledge about cervical cancer (86.5%) and early detection of Pap Smear (89.6%), but only 26.0% had ever had a Pap Smear examination. Bivariate analysis showed that there was no significant relationship between knowledge of cervical cancer and Pap Smear examination (p = 0.503). However, there was a significant relationship between knowledge of early detection of Pap Smear and Pap Smear examination (p = 0.059). Conclusion: Specific and applicable knowledge about Pap Smear has been proven to influence early detection actions, while general knowledge about cervical cancer is not enough to encourage screening actions. Health education should be focused on practical aspects to encourage increased participation of women in cervical cancer screening.